2018
DOI: 10.1523/jneurosci.2693-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Ramping of Dorsal Striatal Pathways preceding Food Approach and Consumption

Abstract: The striatum controls food-related actions and consumption and is linked to feeding disorders, including obesity and anorexia nervosa. Two populations of neurons project from the striatum: direct pathway medium spiny neurons and indirect pathway medium spiny neurons. The selective contribution of direct pathway medium spiny neurons and indirect pathway medium spiny neurons to food-related actions and consumption remains unknown. Here, we used electrophysiology and fiber photometry in mice (of both sexes) to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 63 publications
(41 reference statements)
22
62
0
Order By: Relevance
“…Recently, in freely moving animals, it was reported that both SPN populations become active in localized compact groups of synchronized neurons, that alternate their activity over time (Barbera et al, 2016;Klaus et al, 2017;London et al, 2018), these results are similar to previous slice recordings treated with NMDA . In contrast, slices from DA-depleted animals report neuronal activity locked into a dominant network state with reduced alternations between the assemblies (Jaidar et al, 2010;Lopez-Huerta et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, in freely moving animals, it was reported that both SPN populations become active in localized compact groups of synchronized neurons, that alternate their activity over time (Barbera et al, 2016;Klaus et al, 2017;London et al, 2018), these results are similar to previous slice recordings treated with NMDA . In contrast, slices from DA-depleted animals report neuronal activity locked into a dominant network state with reduced alternations between the assemblies (Jaidar et al, 2010;Lopez-Huerta et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Although there were instances where clear changes in input activity were attributed to the DS onset and lever press, particularly in the GCaMP6s recordings, this activity was not consistent across the different recordings of each input ( Figure S3B). These findings are in line with previous research showing that the most widespread and coherent changes in NAc neuron activity tend to coincide with feeding (London et al, 2018;Nicola et al, 2004aNicola et al, , 2004b.…”
Section: Input Activity On Rewarded Trials Primarily Coincides With Tsupporting
confidence: 93%
“…Electrophysiological recordings in rats performing a similar discriminative stimulus operant task have demonstrated that changes in spiking activity in the NAc are most prevalent and synchronous during food port visits . Also, a recent meta-analysis found that, regardless of the behavioral task, the most prevalent response pattern in the NAc during consumption is a reduction in spiking activity (London et al, 2018). Events preceding consumption, such as operant and approach behavior, are typically associated with sparser and more heterogeneous changes in activity (London et al, 2018;Nicola et al, 2004aNicola et al, , 2004b.…”
Section: Photometry Recordings Of Nac Inputsmentioning
confidence: 99%
“…To constrain the parameter space for initial recordings, we recorded population Ca 2+ activity of putative dSPNs via fiber photometry, reasoning that all aforementioned possibilities could be read out by neural signals within SPNs of the striatum (Fig.7A-C). In support of this idea, we observed value-related signals leading up to trial initiation (Fig.7D,F; Fig.8A,D,H), consistent with population Ca 2+ imaging signals observed in both SPN subtypes as mice approach palatable food (London et al, 2018). While our imaging does not provide the clarity of cellular-level approaches (Donahue et al, 2019; Kwak and Jung, 2019), it clearly demonstrates two phases of activity – a slow ramp occurring ∼10sec.…”
Section: Discussionsupporting
confidence: 81%
“…Recent population Ca 2+ imaging of striatal SPN populations has revealed a prolonged ramping activity prior to action sequence initiation (London et al, 2018). Together with our data (Fig.2) and other work documenting the modulation of initiation latency by prior outcome (Bari et al, 2019), we investigated the preinitiation window as one key timeframe for reward-related signals in dorsal striatal direct pathway neurons.…”
Section: Resultsmentioning
confidence: 99%